The Great political theories - Curtis, Michael 1923-. (New York HarperPerennial ModernClassics, 2008)
Introduced political ideas from Sophocles and Plato to Locke and Montesquieu in vol. 1 and from Burke, Rousseau and Kant to modern times in vol. 2.
v. 1. Comprehensive selection of the crucial ideas in political philosophy from the Greeks to the Enlightenment -- v. 2. Comprehensive selection of the crucial ideas in political philosophy from the French Revolution to modern times.
Originally published: New York: Avon Books, c1981.
Keywords: Political science